Is training effective for older workers? - Matteo Picchio (IZA World of Labor, 2015)
The labor market position of older workers is cause for concern in many industrialized countries. Rapid population aging is challenging pension systems. The recent economic crisis has forced many older adults out of the workforce, into either pre-retirement or non-employment. Encouraging people to work longer and fostering the employability of older workers have become priorities for policymakers. Training specifically designed for older workers might help attain these goals, since it may refresh human capital and reduce the payâproductivity gap. Training older workers might also benefit employers and society as a whole.
Keywords: J14; J24; M53; 330; older workers; training; human capital; employability